Full-Scale Experimental Assessment of a Horizontal-Axis Hydrokinetic Turbine for River Applications: A Challenge for Developing Countries - Edwin Chica; Laura Velásquez; Ainhoa Rubio-Clemente (Energies)
This paper presents an experimental investigation into the performance of a horizontal-axis turbine deployed in the Sinú River. The primary objective is to assess the turbine’s functionality under actual water flow conditions. The prototype is equipped with a rotor measuring 1.58 m in diameter, featuring three blades, which are specifically engineered to produce 1 kW of power at a flow velocity of 1.5 m/s. To evaluate the turbine’s efficiency, measurements of both the electrical power output and the kinetic energy present in the river flow were conducted. The findings reveal a power coefficient (<semantics>CP</semantics>) of 0.4087 for the turbine. Before the integration of hydrokinetic technology can proceed, essential preliminary assessments must be undertaken, including a hydrokinetic energy resource evaluation. This process entails multiple stages of reconnaissance and prefeasibility studies to identify optimal locations along river courses for the technology’s deployment. Additionally, this work highlights the significant challenges associated with adapting hydrokinetic technology in developing nations, particularly in the context of Colombia.